Synthesis and mineralogical characteristics of hydroxylapatite-hydroxylpyromorphite solid solution series Ca5(PO4)3OH – Pb5(PO4)3OH - Motyka, Joanna; Oknińska, Joanna; Manecki, Maciej (Geology, Geophysics and Environment, 2015)
Lead is a widespread environmental contaminant toxic to living organisms. Soils and wastes contaminated with Pb are found in both rural and urban settings. Uptake of Pb from waste, soil or water by phosphate compounds, particularly hydroxylapatite, has been proved as effective remediation strategy (Xu and Schwartz, 1994). The technology arises from the low solubility of lead apatites and from their rapid precipitation reactions. The structure of apatites can be described by the general formula A5(BO4)3C, where A: Ca, Pb, Sr, Ba; B: P, As, V; C: Cl, OH, F, Br, I. Apatites are very tolerant to structural distortion resulting from chemical substitution in cationic and anionic positions and consequently they are remarkably diverse in composition. The hydroxylapatite’s structure also allows for extended substitutions of cations and anions. It is hypothesized here that, thanks to the potential for extensive solid solutions in the system, the lead apatites precipitating in the environment are not pure end members but rather Pb-Ca solid solutions. A complete solid solution between hydroxylapatite (HAP) and hydroxylpyromorphite (HPY) was determined before (Bigi et al., 1991; Hadrich et al., 2001). The results, however, are still fragmentary and partly inconsistent. The objective of the project is systematic characterization (crystal structure as well as infrared and Raman vibrtational properties) of synthetic analogs of the minerals from HAP – HPY solid solution series. This will allow to clarify the controversies. Well characterized products of the synthesis will be used in future in thermodynamic study of solubility changes with substitution, which was never determined before. It is assumed that the properties vary in systematic way with Pb substitution for Ca. An effective wet method of synthesis of Ca-Pb apatites was developed. A crystalline, homogeneous precipitates with stoichiometric composition were produced. Six phases of HAP-HPY solid solution series were prepared by dropwise mixing of a solution containing calcium and/or lead ions and a phosphate solution at room temperature. During the synthesis pH of 8,5 was maintained using NH4OH. Precipitates were washed, air dried and characterized by scanning electron microscopy (SEM/EDS), powder X-ray diffraction,  infrared spectroscopy (FTIR) and Raman spectroscopy. All synthetic products obtained in the experiments form hexagonal needles less than 0.1 µm long. Elemental composition is consistent with theoretical stoichiometry of the phases. X-ray diffraction patterns reveal a shift toward lower angles 2θ for phases with higher lead contents. This indicates an enlargement of the lattice constants. The variation of parameters, however, is not linear (does not follow the Vegard’s law). Particularly the cell parameter c changes more for phases reach in lead. These results are in agreement with those reported previously (Bigi et al., 1991; Hadrich et al., 2001). A shift of band position is also observed in both FTIR and Raman spectra. All the bands shift towards lower wavenumber with increasing Pb content. In most cases the shift is not linear exhibiting two trends similar to lattice parameters. This may indicate that the vibrational properties of the phases in the series depend stronger on the bond length than on the atomic mass of substituting elements. This work was supported by AGH-UST statutory grant No. 11.11.140.319.